PROSPECTIVE TEACHERS’ ABILITY IN MATHEMATICAL PROBLEM-SOLVING THROUGH REFLECTIVE LEARNING - Yunika Lestaria Ningsih; Rohana Rohana (IKIP Siliwangi and I-MES, 2016)
The research aims to determine the mathematical problem-solving ability of prospective teachers’ through reflective learning. Reflective learning is a learning process that provides students the opportunity to examine and investigate the problems that is triggered by experience, analyzing of individual the experiences, and facilitate the learning of the experiences. These lessons are identified to improve mathematical ability students. By using a descriptive qualitative research. The subject of this study were students of Mathematics Education Program in one of private universities in Palembang, consisting of 34 students. This study was conducted in odd semester academic year of 2015/2016. The instruments in this study were mathematical problem-solving ability test, observation sheet, and interview guide. The data were analyzed descriptively. Based on analysis of the data are found that the average mathematical problem-solving ability of students’ through reflective learning in good categories.